2021
DOI: 10.3390/nu13041126
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Vitamins D2, D3, D4, D5, D6, and D7 Solubilized in Mixed Micelles by Human Intestinal Cells, Caco-2, an Enhancing Effect of Lysophosphatidylcholine on the Cellular Uptake, and Estimation of Vitamins D’ Biological Activities

Abstract: Vitamins D have various biological activities, as well as intestinal calcium absorption. There has been recent concern about insufficient vitamin D intake. In addition to vitamins D2 and D3, there are lesser-known vitamins D4–D7. We synthesized vitamins D5–D7, which are not commercially available, and then evaluated and compared the mixed micelles-solubilized vitamins D uptake by Caco-2 cells. Except for vitamin D5, the uptake amounts of vitamins D4–D7 by differentiated Caco-2 cells were similar to those of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 130 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…Significantly, Caco-2 permeability experiments showed that LipoMicel ® is 12,000 times more permeable compared to the baseline control (Table 3 and Figure 4). This is several orders of magnitude higher than the 2.5 times enhanced uptake reported on lysophosphatidylcholine micelles [30], the 4-fold increase in bioavailability reported in a casein micelles [47] and the 5.3-fold increase reported in pea-protein-based nanoemulsions [48]. However, in this study it appears that the increased permeability of micellar Vitamin D 3 does not correlate with increased solubility or reduced particle size-since LipoMicel has similar solubility characteristics (Figure 2) and particle size distribution (Figure 5 and Table 4) as the baseline control.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Significantly, Caco-2 permeability experiments showed that LipoMicel ® is 12,000 times more permeable compared to the baseline control (Table 3 and Figure 4). This is several orders of magnitude higher than the 2.5 times enhanced uptake reported on lysophosphatidylcholine micelles [30], the 4-fold increase in bioavailability reported in a casein micelles [47] and the 5.3-fold increase reported in pea-protein-based nanoemulsions [48]. However, in this study it appears that the increased permeability of micellar Vitamin D 3 does not correlate with increased solubility or reduced particle size-since LipoMicel has similar solubility characteristics (Figure 2) and particle size distribution (Figure 5 and Table 4) as the baseline control.…”
Section: Discussionmentioning
confidence: 61%
“…Efforts in this regard have generally been directed toward increasing solubilities by reducing the particle size of the delivery vehicles and creating nanoparticles and nanostructured lipid carriers [27][28][29]. However, in addition to particle size, there is increasing evidence that cell-matrix adhesion and specific receptor carriers may also play key roles in influencing absorption by using micellar delivery systems [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the enterocytes, lipids are resynthesized and assembled into chylomicrons and high density lipoproteins for secretion [47]. The physiological pathway of fat digestion and uptake has gained increasing attention in drug development, as micelles can act as nanocarriers promoting the oral absorption of hydrophobic drugs and nutrients [21,48,49], and association of drugs with chylomicrons might prevent metabolic inactivation by avoiding the hepatic first-pass liver metabolism, as chylomicrons are transported via the lymphatic circulation [4]. Alternatively, enterocyte lipid metabolism may be targeted pharmacologically to lower systemic lipid load and energy intake, thus affecting hyperlipidemia, obesity, metabolic syndrome, steatosis, insulin resistance, atherosclerosis and other disorders [5,47].…”
Section: Intestinal Nutrient Absorptionmentioning
confidence: 99%
“…A prior study sought to determine if it was possible to prevent a vitamin D deficiency by increasing the intake of vitamins D2-D7 [49]. For vitamin D to work in the body as a nutrient or functional ingredient, it must first be absorbed through the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%